Combined Ultrasonic and Thermal Treatment: Effects on Microbial Reduction and Protein Stability in Fresh Milk - Lee, Mei Chi; Handayani, Atul; Po, Sing Huat (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to evaluate the effect of ultrasonic treatment combined with temperature variation on the inhibition of Escherichia coli and the preservation of protein content in fresh cow’s milk under controlled experimental conditions. Methodology: Experimental design; ultrasonic generator (60 kHz, 70 W); water bath temperature control (30°C, 40°C, 50°C); incubator shaker; laminar air flow; Total Plate Count (TPC) method; Kjeldahl method; colony counter; Nutrient Agar (NA) and Nutrient Broth (NB); two-way ANOVA; descriptive statistics; statistical software (SPSS). Main Findings: Ultrasonic treatment combined with temperature significantly reduced Escherichia coli counts, with the highest reduction (95.9%) achieved at 50°C for 30 minutes. Bacterial counts decreased progressively with increasing temperature and exposure time. Protein content remained relatively stable, ranging from 2.02% to 2.20%, indicating minimal degradation under treatment conditions. Novelty/Originality of this study: This study presents an integrated and statistically validated approach to simultaneously analyze microbial inactivation and protein stability using combined ultrasonic and thermal treatments. It demonstrates a synergistic interaction between acoustic cavitation and moderate temperature, offering a novel framework linking physical wave principles with biological systems in food processing.